THE ROLE OF SHAMAN CHIKITSA IN EKAKUSHTHA WITH SPECIFIC REFERENCE TO PSORIASIS: A CASE STUDY - Sushir Pavan Dnyandeo,; Umate Pooja Suresh,; Chawre Sushil Vilas, (International Journal of Ayurveda and Pharma Research, 2021)
Skin diseases are increases day by day due to unhealthy food habits and life style changes. People are also very cautious about the skin problem because of skin is the mirror which reflects the harmony of internal functions of body. Any change in skin color disturbs the patient both mentally and physically. Psoriasis is chronic inflammatory, hyperproliferative skin disease. It is an autoimmune disease in which scaling and itching of skin present. Because of its recurrent nature the disease has remained a great problem. There is no definite cure for this disease till now. Modern medicine provides symptomatic relief but also has side effects in long course.Here an effort was made to treat a sixty-four years old male diagnosed case of Plaque Psoriasis, by combined Ayurvedic regimen. The Ayurvedic diagnosis is considered as Ekakushtha which is a Vata Kapha predominant Kshudrakushtha. As the principle of treatment, all types of Kushtha will be treated with Samshodhana and Samshamana. In Covid pandemic, Shamana Chikitsa was preferably given for 45 days. PASI (Psoriasis area severity index) score was taken for assessment criteria. PASI score before starting the treatment was found to be 9.6 which decreased to 0.4 at the end of treatment. Also, significant improvements in subjective parameters were observed.This case report showed that combined Ayurvedic modalities resulted in great improvement in overall condition of the patient with no recurrence in five months follow-up. Such a combine Ayurvedic modalities can be very useful in the management of Psoriasis and betterment of mankind.